The synergy of The Corruption Eradication Commission, police, and prosecutors in the eradication of corruption crimes - Asrullah - - (Indonesia Prime, 2019)
In the process of development can cause progress for the community and can also lead to changes in social conditions of the community that have a social impact, especially concerning the problem of increasing criminal acts that are troubling the community. One criminal offense that can be said to be phenomenal and seize the attention of society is a criminal act of corruption. This criminal offense not only harms the state's finances but is also a violation of the social and economic rights of society. Corruption is also a violation of the community's beliefs. It can say that the characteristics of the behavior of corruption, among others, adequate education, has a high social status, rich and influential in society, and has authority, both in government and in private enterprises